Comparison of 14 body size variables on adult skeletal age methods: how body mass, BMI, fat and muscle influence age estimations - Catherine E. Merritt (Taylor & Francis Group, 2020)
Background: Skeletal age estimations consistently under-age individuals with low body mass and over-age individuals with high body mass. Aim: To assess the directional biases of body size variables, including fat and muscle tissue, on skeletal age estimates. Subjects and methods: CT scans of 420 age- and size-selected cadavers were assessed using the fourth rib and pubic symphysis age estimation methods. MANCOVA was used to test the effects of stature, body mass, circumference, and fat and muscle tissue area on age estimation biases. Results: For both methods, there were biases based on body mass, BMI, circumference and fat tissue area. Individuals with the lowest measurements for these variables were under-aged while individuals with the highest measurements were over-aged. Age estimation biases were not affected by stature, muscle area, or skeletal measurements of bi-iliac breadth, femoral head diameter, or femoral length. Conclusion: Increased body mass, and specifically fat tissue, accelerates skeletal ageing. Increased muscle area generally did not show a protective effect on skeletal ageing. The accuracy of age estimations would be improved by factoring in body mass. However, femoral head diameter and bi-iliac breadth are not good proxies for body mass. Osteological markers of obesity offer a promising new approach.